2018
DOI: 10.1111/jace.16228
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ba2+ consumption and intermediate dwelling during processing of YBa2Cu3O7 nanocomposite films

Abstract: Achieving high-critical current densities (J c ) with small artificial pinning centers is a crucial challenge for YBa 2 Cu 3 O 7−δ (YBCO) nanocomposite thin films fabricated using chemical solution deposition methods. In this work, the YBCO texture, structure purity, and its J c properties were improved by understanding the influence of preformed ZrO 2 nanocrystals (Ba 2+ consumption) during the nucleation and growth mechanism. This comprehensive study leads to an additional intermediate dwelling step during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…This means that HfO 2 nanocrystals reacted with the Ba 2+ ions, leading to the formation of BaHfO 3 particles in the YBCO matrix. Nevertheless, our previous work [39] demonstrated that the reactivity of preformed ZrO 2 nanocrystals results in a delay rather than in a degradation of the YBCO nucleation and growth. This growth delay can be circumvented via the introduction of an intermediate dwelling step, yielding an increase of J c [39].…”
Section: Multi-deposition Of Hfo 2 -Ybco Inksmentioning
confidence: 94%
See 3 more Smart Citations
“…This means that HfO 2 nanocrystals reacted with the Ba 2+ ions, leading to the formation of BaHfO 3 particles in the YBCO matrix. Nevertheless, our previous work [39] demonstrated that the reactivity of preformed ZrO 2 nanocrystals results in a delay rather than in a degradation of the YBCO nucleation and growth. This growth delay can be circumvented via the introduction of an intermediate dwelling step, yielding an increase of J c [39].…”
Section: Multi-deposition Of Hfo 2 -Ybco Inksmentioning
confidence: 94%
“…Nevertheless, our previous work [39] demonstrated that the reactivity of preformed ZrO 2 nanocrystals results in a delay rather than in a degradation of the YBCO nucleation and growth. This growth delay can be circumvented via the introduction of an intermediate dwelling step, yielding an increase of J c [39]. However, Pop et al [34] has recently printed a low-fluorine-based YBCO precursor solution with additives on a LaAlO 3 substrate with a final thickness of 0.6-1.2 µm via a single deposition, yielding a fairly good J c value of 2.0-2.7 MA•cm −2 and an I c value of 240 A at 77 K ( Table 2).…”
Section: Multi-deposition Of Hfo 2 -Ybco Inksmentioning
confidence: 94%
See 2 more Smart Citations
“…Apart from the benefits of RE mixing, and in order to improve the pinning properties in such films further, secondary phases can be included in the matrix to produce REBCO nanocomposites. This topic has been extensively studied by many groups evidencing that the in-field transport properties of REBCO films can be extensively enlarged by using both the "in situ" and the "ex situ" approaches [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%